ANALISIS TINGKAT EFEKTIVITAS DAN KONTRIBUSI PENDAPATAN ASLI TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN BERAU: ANALISIS TINGKAT EFEKTIVITAS DAN KONTRIBUSI PENDAPATAN ASLI TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN BERAU - Verenika Geovani (ECO-BUILD, 2020)
The purpose of this study refers to the formulation of the problem raised by the researcher, namely: to find out the effectiveness of management and the contribution of the Local Own-source Revenue to Berau district's Local government budget on average from 2011 to 2018. This study aims to provide information to the Berau District Government regarding the effectiveness of the management and contribution of the Regional Original Revenue to the Berau Regency Regional Revenue and Expenditures on average from 2011 to 2018. The results showed that the first hypothesis stating the management of the Berau Regency's Original Revenue, on average during 2011 to 2018 was "quite effective" which was rejected, because based on the results of an analysis of the average financial management of the Original Regions was 119, 27% were in the interval " Very effective". The second hypothesis which was stated as the alleged contribution of the Original Regional Revenues to the Regional Budget Revenues and Expenditures in the Berau District on average from 2011 to 2018 "quite good" was also questioned, because based on the analysis results of the Berau District Revenue and Expenditure was 10.24% are in the "Less" interval.